High-dose interleukin-2 (HD IL-2) for advanced melanoma: a single center experience from the University of Pittsburgh Cancer Institute. Issue 1 (19th September 2017) - Davar, Diwakar; Ding, Fei; Saul, Melissa; Sander, Cindy; Tarhini, Ahmad A.; Kirkwood, John M.; Tawbi, Hussein A.
Abstract : Background: Durable remissions are observed in a fraction of metastatic melanoma patients treated with high-dose interleukin-2 (HD IL-2). Early studies reported overall (OR) and complete response (CR) rates of 16% and 8% respectively. Toxicity limited use to specialized centers with standardized protocols. We report on 243 patients treated at the University of Pittsburgh in a non-intensive care unit (ICU) oncology specialty setting. Methods: Clinical and radiological data were collected on 243 patients treated between 1992 and 2015. Each HD IL-2 cycle was given over 5 days, cycles were repeated after 9 days and courses (2 cycles) were repeated every 6–9 weeks in patients with stable or responding disease, for up to 3 courses total. Influence of baseline characteristics on outcomes was assessed using Kaplan-Meier estimates and Cox proportional hazards analysis. Results: Two hundred forty-three patients received 692 cycles (5270 doses) between 1992 and 2015. Two hundred thirty-seven patients were evaluable for response: OR rate 18.1% with CR rate 8.0%. Median overall survival (OS) 9.6 months in the entire cohort but 64.9 months in responders. Median number of cycles delivered was 2, and median number of doses per cycle was 8. Toxicity was consistent with prior reports. HD IL-2 required ICU transfers in 11 patients and 1 death was attributed to HD IL-2. Pre-treatment lactate dehydrogenase (LDH) levels correlated significantly with progression-free survival [1-2× upper limit normal (ULN) HR 1.95; >2× ULN HR 2.32] and overall survival (1-2× ULN HR 1.67; >2× ULN 2.49). Response to HD IL-2 and site of metastatic disease also correlated significantly with progression-free and overall survival. Conclusions: In this large series of patients spanning more than two decades, OR/CR rates with HD IL-2 were 18.1%/8.0% respectively. Toxicity data was consistent with prior reports. Pre-treatment LDH values and site(s) of metastatic disease may be useful markers to select patients at greater likelihood of benefit to HD IL-2 therapy.